Translating Trauma through Gustatory Memorial: A Reading of the Post-Partition Narrative in Kallol Lahiri’s Indubala Bhater Hotel - Kuheli Singha (ILN Journal: Indian Literary Narratives, 2025)
The indelible marks that the horror of the Partition and its resultant mass exodus left on the two states of Punjab and Bengal are still felt. The nature of the experience of pathological violence in Punjab has been somewhat different from the psychological trauma that Bengal experienced. The immediacy of visceral violence on the Bengal border did not exceed its counterpart in Punjab; rather, the experience has sedimented into a long-lasting psychological state of unsettlement. This vivid presence of traumatic memory as an everyday reality, however, goes unrecognised within the fold of documented history, resulting in a cultivated amnesia or “memocide” of the minorities. Kallol Lahiri’s Indubala Bhater Hotel (2020) situates this lingering sense of loss and displacement within the everyday realm of culinary practices, where food becomes a symbolic and material site of memory. Drawing on Memory Studies, Trauma Studies, and Food Studies, this paper explores how Lahiri’s narrative reconfigures the Partition through concepts such as Marianne Hirsch’s “postmemory,” Ananya Jahanara Kabir’s “post-amnesia,” and David Sutton’s “gustemology.” The analysis foregrounds the ways in which food, as both  sensory and symbolic medium, enables the transmission of traumatic memory across generations. This article seeks to enquire into the ways culinary practices synthesise with the traumatic past in articulation of the otherwise unspeakable memory of uprootedness.